Combination of noncovalent conformational locks and side chain engineering to tune the crystallinity of nonfullerene acceptors for high-performance P3HT based organic solar cells. (2nd November 2018) - Ye, Pan; Chen, Yusheng; Wu, Jianfei; Wu, Xiaoxi; Xu, Yunxiao; Li, Zijie; Hong, Shikai; Sun, Ming; Peng, Aidong; Huang, Hui
Abstract : The performances of P3HT based OSCs were systematically improved attributed to the modification of the side chains of small molecules. Abstract : P3HT-based organic solar cells (OSCs) have great advantages for commercialization including straightforward and scalable synthesis and well-developed roll-to-roll manufacturing technology. However, it is difficult to control the morphology of P3HT:acceptor blend films due to their highly crystalline characteristics. In this work, we designed and synthesized two thiazole (Tz) containing small molecular acceptors with an A–π–D–π–A type structure for the P3HT donor material. Both small molecules exhibit a good planar configuration due to incorporation of S⋯N noncovalent conformational locks. Upon changing the side chains, the interchain π–π stacking and the crystallinity of the small molecules were fine-tuned. Interestingly, P-IDTzR with bulky side chains exhibits suitable crystallinity, which matches well with P3HT. As a result, the P3HT:P-IDTzR blend films demonstrate optimal morphology, leading to a larger short circuit current ( J SC ), an enhanced fill factor (FF), and thus a larger power conversion efficiency (5.01%). This contribution provides important guidance in designing nonfullerene acceptors for high-performance P3HT based OSCs.